Increasing Rural Household Income through Human Resources Empowerment and Capacity Building to Overcome Stunting - Neno, Marianus S.; Manongga, Irience R.A.; Kamuri, Klaasvakumok J.; Aman, Dominikus Kopong T.; Nenohai, Marylin E.S. (International Journal Labs, 2023)
ackground: Low levels of education and livelihoods have an impact on household income/income. In general, the biggest expenditure of households with low incomes is for food needs, which if viewed further, is mostly on staple food so that there is an imbalance in household consumption which is eventually alleged to be the cause of malnutrition, especially in children. Aim: This study aims to determine strategies for increasing rural household income through empowerment and capacity building of household human resources as an effort to overcome stunting. Method: This is a case study with a qualitative approach. It attempts to capture reality as holistic, complex, dynamic, meaningful and the relationship is interactive/reciprocal. The types of data used in this study are quantitative data types and qualitative data types of required data sources, namely primary data and secondary data. The data needed were collected by means of in-depth interviews, observations, documentation. Findings: The government seeks to overcome stunting in Kupang, TTS and Manggarai Regencies by empowering the community through several stages such as the first stage, namely making the community aware of the importance of increasing self-capacity, in the second stage, namely the transformation stage, opening people's insights in the form of basic knowledge and skills about the role taken in development in the household and in the community. The last or third stage is the improvement of intellectual abilities ranging from skills to skills that can form initiatives and innovation so that it can usher in a pattern of independence.